EVIDENCE OF ANOPHELES RESISTANCE TO PYRETHROID PESTICIDES: REPORT FROM GADAU KATAGUM ENDEMIC REGION BAUCHI STATE, NIGERIA - Muhammad, Sani Sade; Muhammad , Mahe Mukhtar; Alhaji, Jibril Abdullahi; Musa, Amina Ladidi (FUDMA JOURNAL OF SCIENCES, 2025)
Malaria continues to pose a significant health issue negatively. The high number of cases requires prevention, including controlling the Anopheles gambiae s.l., mosquito. One of the control methods is the use of insecticides containing pyrethrin. WHO tube Bioassays in Anopheles gambiae s.l., to determine resistance from pyrethroids expose in F1 adult mosquitoes to insecticides and a sensitivity test to temephos, measuring the activity of non-specific alpha and beta esterase enzymes. This study determined Anopheles gambiae s.l., resistance from larvae to adult. The bioassay was used for the temephos sensitivity of Anopheles larvae. The LC99 value was analyzed using probit and compared with the diagnostic. WHO susceptibility test was conducted to determine pyrethroid resistance from adult mosquitoes. A mortality of less than 90% was declared as resistant. Measurement of alpha and beta esterase levels used Lee’s microplate assay technique based on visual identification and absorbance value. Anopheles gambiae s.l., were resistant to both class of pyrethroids. Adult mosquitoes have recorded resistant to both class of type i and ii pyrethroid with increase in time reaching about 60% with cypermethrin. At 24 hours Mortality Rates showed Cypermethrin with the highest at 90% followed by Permethrin (80%), Deltamethrin (75%), and Tetramethrin (70%). Based on the alpha esterase activity test, it was found that most of the mosquitoes showed very sensitive meanwhile, most of the mosquitoes were moderate resistance. This study suggests that Anopheles gambiae s.l., the population from the endemic region in Bauchi, Nigeria are indicated to develop resistance to the pyrethroids insecticides.